A brief review on human mtDNA mutations and NRTI-associated mtDNA toxicity and mutations. (3rd May 2016) - Chattopadhyay, Koushik; Aldous, Colleen
Abstract: Mitochondrion is a cellular organelle that is present in most of the cells and is responsible for producing energy for the cell. Mitochondria have their own double-stranded DNA genome which is distinct from nuclear genome. The replication, recombination and repair of mtDNA are achieved by DNA polymerase-gamma which is encoded by POLG gene. Mutation in the mtDNA or POLG gene might lead to mitochondrial dysfunction and disease. Several mutations and polymorphisms in these regions have been associated to mitochondrial disorders. Nuceloside and nucelotide reverse transcriptase inhibitors (NRTIs) that form the basis of AIDS therapy have significantly increased the survival rate of HIV-infected individuals predisposing them to other side effects. One of the most common side effects of NRTI usage is mitochondrial toxicity leading to several mitochondrial disorders. Mutations in mtDNA have also been associated to the use of specific NRTIs leading to specific mitochondrial disorders. This review briefly summarizes the advances in mtDNA mutations and NRTI-caused mitochondrial toxicity and mutations.